Propriedades físicas do modelo de Ising bidimensional - Abreu, Henrique Borges de (Universidade Federal de São Carlos, 2025)
In this work, we presents the studies about the thermodynamical properties of the bidimensional Ising model, obtained by Lars Onsager and C.N. Yang. This model describes the ferromagnetism based on the interaction among magnetic dipoles within a crystal. This way, it is presented the computation of the free energy, inner energy and specific heat at zero magnetic field via representation theory. It results in the determination of the critical point. Later on, it is discussed the computation of magnetization, which clear exhibit the phase transition.
Physical properties of the bidimensional Ising model
Keywords: Ising model; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::FISICA ESTATISTICA E TERMODINAMICA; 4. Educação de Qualidade